Analisis Pengaruh Uang Elektronik, Inflasi, dan Suku Bunga terhadap Jumlah Uang Beredar di Indonesia - Cindy Sucitra Sitanggang; P. Eko Prasetyo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The money supply becomes a concern if not properly controlled, as an imbalance may lead to inflationary pressure, price instability, and disruption of overall economic performance. Controlling the money supply is therefore essential for maintaining macroeconomic stability. In monetary policy, electronic money affects the level of money circulating in the economy. In addition, inflation and interest rates are also key factors that can affect the money supply. Thus, the objective of this study is to analyze the influence of electronic money, inflation, and interest rates on the money supply in Indonesia during the period from the first quarter of 2016 to the fourth quarter of 2023. Using secondary data and multiple linear regression analysis. The findings show that electronic money and inflation have a significant positive impact on the money supply, while interest rates have a significant negative effect. Overall, electronic money, inflation, and interest rates collectively have a significant influence on the money supply.